Disulfide bond reduction and exchange in C4 domain of von Willebrand factor undermines platelet binding - Kutzki, Fabian; Butera, Diego; Lay, Angelina J.; Maag, Denis; Chiu, Joyce; Woon, Heng-Giap; Kubař, Tomáš; Elstner, Marcus; Aponte-Santamaria, Camilo; Hogg, Philip J.; Gräter, Frauke (Journal of thrombosis and haemostasis, 2023)
Background - The von Willebrand factor (VWF) is a key player in regulating hemostasis through adhesion of platelets to sites of vascular injury. It is a large, multi-domain, mechano-sensitive protein that is stabilized by a net of disulfide bridges. Binding to platelet integrin is achieved by the VWF-C4 domain, which exhibits a fixed fold, even under conditions of severe mechanical stress, but only if critical internal disulfide bonds are closed. - Objective - To determine the oxidation state of disulfide bridges in the C4 domain of VWF and implications for VWF’s platelet binding function. - Methods - We combined classical molecular dynamics and quantum mechanical simulations, mass spectrometry, site-directed mutagenesis, and platelet binding assays. - Results - We show that 2 disulfide bonds in the VWF-C4 domain, namely the 2 major force-bearing ones, are partially reduced in human blood. Reduction leads to pronounced conformational changes within C4 that considerably affect the accessibility of the integrin-binding motif, and thereby impair integrin-mediated platelet binding. We also reveal that reduced species in the C4 domain undergo specific thiol/disulfide exchanges with the remaining disulfide bridges, in a process in which mechanical force may increase the proximity of specific reactant cysteines, further trapping C4 in a state of low integrin-binding propensity. We identify a multitude of redox states in all 6 VWF-C domains, suggesting disulfide bond reduction and swapping to be a general theme. - Conclusions - Our data suggests a mechanism in which disulfide bonds dynamically swap cysteine partners and control the interaction of VWF with integrin and potentially other partners, thereby critically influencing its hemostatic function.
Online verfügbar: 12. April 2023, Artikelversion: 17. Juli 2023
Gesehen am 05.10.2023